(3GdeSFhdjI GdeOfjI Yf CVQGQ CHQGL GdghGJa GdfbGdI (B/ s - (3SjO QGTO YHOGdbGOQ Hjheis; (3YHOGdgGOi ahRi GdYhVi s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2021)
(3JfGhdfG GdeSFhdjI GdeOfjI Yf CVQGQ CHQGL GdghGJa GdfbGdI(B: (3h Je JbSje GdQSGdI Edi HGHjf jSHbgeG aUd JegjOi JYQVfG ajg ddCHQGL h GdCYeOI GdehaQI dNOeI GdGJUGdGJ(B: (3h bSefGg Edi eHMKjf(B: (3GdChd WHjYI Yed CHQGL GdghGJa GdfbGdI h fWGb JCKjQgG(B: (3h GdKGfi GdJCKjQGJ GdHjhdhLjI dCHQGL GdghGJa GdfbGdI h GdETYGYGJ GdefHYKI efgG(B: (3h JYQVfG ai GdHGH GdChd dJMOjO GdeSFhdjI GdeOfjI GdfGTFI Yf CVQGQ CHQGL GdghGJa GdfbGdI(B: (3h bSefGg Edi KdGKI aUhd(B: (3JMOKfG ai GdChd Yf GdeSFhdjI GdYbOjI GdfGTFI Yf CVQGQ CHQGL GdghGJa GdfbGdI(B: (3h JMOKfG ai GdKGfi Yf GdeSFhdjI GdJbUjQjI Yf CVQGQ CHQGL GdghGJa GdfbGdI(B: (3h ai GdKGdK Yf GdeSFhdjI GdehVhYjI Yf CVQGQ CHQGL GdghGJa GdfbGdI(B: (3h ai GdHGH GdKGfi JfGhdfG CMcGe GdeSFhdjI GdeOfjI GdfGTFI Yf CVQGQ CHQGL GdghGJa GdfbGdI(B: (3h bSefGg Edi aUdjf(B: (3JYQVfG ai GdChd dOYhi GdeSFhdjI GdfGTFI Yf CVQGQ CHQGL GdghGJa GdfbGdI(B: (3h CNjkQG ai GdaUd GdKGfi JcdefG Yf GdJYhjV cCKQ Yf CVQGQ CHQGL GdghGJa GdfbGdIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdeOfi, (B2021s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B390-418s
Keywords: (3GdbGfhf GdeOfjs; (3CHQGL GdghGJa GdfbGdIs; (3GdeSFhdjI GdeOfjIs; (3GdJCKjQGJ GdHjhdhLjIs; (3ETYGYGJs; (3GdGdJRGeGJ GdegfjI hGdYbOjIs; (3TQcI GdGJUGdGJs; (3GdJMPjQs; (3GdCVQGQ GdcgQheZfGWjSjIs; (3GdghGFjGJs; (3GdVQQs; (3eVGQ GdLhGQ ZjQ GdeCdhaIs; (3CVQGQ CHQGL GdGJUGdGJs; (3ehba GdbVGA GdaQfSjs; (3GdGdJRGe HGdMjWIs; (3GdeNGWQ GdcgQheZfGWjSIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs